2021
DOI: 10.32047/cwb.2021.26.4.6
|View full text |Cite
|
Sign up to set email alerts
|

Elevated temperature study on geopolymer concrete with ferrochrome slag aggregates

Abstract: This paper deals with the strength and mass loss of geopolymer concrete in comparison with conventional cement concrete after elevated temperature exposure. In this study, the coarse aggregates of the conventional geopolymer concrete are replaced partially (40%) with ferrochrome slag aggregates, to obtain the replacement mix of geopolymer concrete. The microstructure of geopolymer concrete was examined by XRD, X-ray tomography, and SEM and also discussed in this paper. The results concluded that after exposure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…The application of gels in concrete became a hot topic, and many researchers focus on the study of compressive strength, which is an important property of geopolymer concrete [ 24 ]. In order to explore the impact of high-temperature exposure on the strength and quality loss of ordinary concrete and geopolymer concrete, Indu et al [ 25 ] carried out research using XRD, X-ray, and SEM methods, and the results show that the strength loss of ordinary concrete under high temperature exposure was about 18% higher than that of geopolymer concrete. Khoa et al [ 26 ] proposed to evaluate the strength of fly ash-based geopolymer concrete using the deep neural network (DNN) and res net architecture to solve the shortcomings of the long time and high cost of traditional laboratory experiment methods.…”
Section: Introductionmentioning
confidence: 99%
“…The application of gels in concrete became a hot topic, and many researchers focus on the study of compressive strength, which is an important property of geopolymer concrete [ 24 ]. In order to explore the impact of high-temperature exposure on the strength and quality loss of ordinary concrete and geopolymer concrete, Indu et al [ 25 ] carried out research using XRD, X-ray, and SEM methods, and the results show that the strength loss of ordinary concrete under high temperature exposure was about 18% higher than that of geopolymer concrete. Khoa et al [ 26 ] proposed to evaluate the strength of fly ash-based geopolymer concrete using the deep neural network (DNN) and res net architecture to solve the shortcomings of the long time and high cost of traditional laboratory experiment methods.…”
Section: Introductionmentioning
confidence: 99%
“…The mineral phases of the slag are mainly magnesium olivine (MgSiO4), magnesium-chromium spinel [Mg(Al 1.5 Cr 0.5 )O 4 ], and magnesium-aluminum spinel (MgAl 2 O 4 ). Therefore, the high carbon ferrochrome slag has low activity, and it can be used as concrete aggregate [ 5 , 6 , 7 , 8 , 9 ]. It has been shown that, by adjusting the firing temperature and the composition of raw materials, the spinel phase in ceramics can reduce the leaching of Cr very well [ 10 ].…”
Section: Introductionmentioning
confidence: 99%